An evaluation of URA's registry file system : a study of information needs of land planners in Singapore. - Foo, Eng Yong. (2008)
The main objective of this research was to evaluate the Urban Redevelopment Authority's (URA) registry automated file management system and find out how the system could be improved to meet the information needs of Land Planners. The Registry in URA used manual system to manage its file records, tracking their movements and locating relevant file records for their officers in the last two decades.